Impact of Physical and Cognitive Exertion on Cognitive Control - Davranche, Karen; Tempest, Gavin D.; Gajdos, Thibault; Radel, Rémi (Frontiers in Psychology, 2018)
In a recent study, the differential effects of prolonged physiologically challenging exercise upon two executive processes (cognitive control and working memory) have been investigated. However, the impact of exercise on the selective inhibition task remained debatable and needed further analysis to dissociate the effects induced by exercise intensity from those induced by the time spent on task upon cognitive control outcomes. In this study we propose a thorough analysis of these data, using a generalized mixed model on a trial-by-trial basis and a new measure of the strength of the automatic response based on reaction time distribution, to disentangle the effect of physical fatigue from cognitive fatigue. Despite the prolonged duration of exercise, no decline in cognitive performance was found in response to physical fatigue. The only change observed over the 60-min exercise was an acceleration of the correct trials and an increase of errors for incompatible trials. This pattern, similar in both exercise conditions, supports the occurrence of cognitive fatigue induced by the repetition of the cognitive tasks over time.